1991
DOI: 10.1007/bf02540210
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic bacteria of the freshwater neuston and their ability to act as plasmid recipients under nutrient deprived conditions

Abstract: Significantly higher numbers of Gram-negative heterotrophic bacteria were present at the air-water interface (neston) of freshwater lakes than in the bulk water. Neuston bacteria were distinguished as a population distinct from bacteria in the bulk water by a higher incidence of pigmented colony types and significantly greater levels of multiple resistance to antibiotics and heavy metals. The incidence of plasmids in 236 neuston and 229 bulk water strains were similar (14 and 16.2%, respectively). Nine of 168 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…Examples of such natural hot spots are the scum layers on standing bodies of water and the surface microlayers (SML) in lakes and oceans (17,28). Our postulate is corroborated by various studies that observed plasmid transfer or detected plasmids in such natural ecosystems (4,19,20,32,38,44). There are multiple possible explanations for the observed increased plasmid transfer at the air-liquid interface compared to that in submerged biofilms, and they likely involve a combination of the physical properties of the environment as well as the physiological state of the cells.…”
Section: Discussionsupporting
confidence: 72%
“…Examples of such natural hot spots are the scum layers on standing bodies of water and the surface microlayers (SML) in lakes and oceans (17,28). Our postulate is corroborated by various studies that observed plasmid transfer or detected plasmids in such natural ecosystems (4,19,20,32,38,44). There are multiple possible explanations for the observed increased plasmid transfer at the air-liquid interface compared to that in submerged biofilms, and they likely involve a combination of the physical properties of the environment as well as the physiological state of the cells.…”
Section: Discussionsupporting
confidence: 72%
“…5B to D) indicate that a freshwaterenvironment AWI bacterial community was quite distinct from the subsurface community directly beneath it. Other less-specific collection methods for freshwater (11) and marine (16) surface microorganisms have provided qualitative data that have resulted in conclusions similar to those found in the present study but with no correlative microscopic data.…”
supporting
confidence: 75%
“…This is why many studies have been recently carried out to determine the distribution of antibiotic resistance bacteria in freshwater basins, estuaries, municipal drinking water and sewage waters (Niemi et al, 1983;Calomiris et al, 1984;Jones et al, 1991;Herwig et al, 1997;Ash et al, 2002;Mudryk, 2002). However, relatively very few studies on antibiotic resistance bacteria in marine water (Nair et al, 1992;Mudryk and Skorczewski, 1998) and only very less studies have been undertaken in dynamic ecosystem such as mangrove environment.…”
Section: Introductionmentioning
confidence: 99%